Shortages of innovation support organisations in the Basque country - Leire Ozerin; Eva Velasco (European Regional Science Association (ERSA), 1998)
Increasing competition, internationalisation of the strategies in a context of economic globalisation: these are the difficult conditions in which the activity of an increasing number of SMEs (two thirds of the European Union enterprises) have to deal with. For many of them, even if the activity they carry out is in a traditional branch, the innovation can be a decisive competitive advantage. The many market failures that appear in that innovation process has lead to the different levels of government to intervene through Technology Policies in order to correct those imperfections. The aim of this paper is to analyse those public interventions, focusing on the case of the Basque Country?s Government Innovation strategy since the 80?s. During these two decades this policy has experienced several changes, some of them in the right direction (like the integration of science and technology policy), while others do not achieve yet to solve the lack of involvement of a big proportion of SMEs in those R&D policies and neither to make them relate with most of the Basque Technology Transfer Agencies. In this sense, of the 13,054 manufacturing enterprises of the Basque Country (75% of them with less than 10 employees), nowadays only 318 carry out R&D activities, which means that the government policy only reaches to the group of firms that would find the way also without any external help. It is this dualism the major problem that has been identified thanks to the data obtained through our research in the "Regional Innovation Systems: designing for the future" project funded by the European Commission.
Keywords: 330